2015
DOI: 10.1016/j.apal.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Connected components of definable groups, and o-minimality II

Abstract: We give examples of definable groups G (in a saturated model, sometimes o-minimal) such that G 00 = G 000 , yielding also new examples of "non G-compact" theories. We also prove that for G definable in a (saturated) o-minimal structure, G has a "bounded orbit" (i.e. there is a type of G whose stabilizer has bounded index) if and only if G is definably amenable, giving a positive answer to a conjecture of Newelski and Petrykowski in this special case of groups definable in ominimal structures. We also introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 25 publications
(65 reference statements)
3
65
0
Order By: Relevance
“…In [3], the authors have shown that such extensions can, under some additional assumptions, give new examples of definable groups with G 00 = G 000 , building upon and extending the intuitions from the first known example with this property, found in [5], namely the universal cover of SL 2 (R). They also pose some questions and conjectures, one of which will be proved at the end of this section.…”
Section: ( † †)mentioning
confidence: 93%
“…In [3], the authors have shown that such extensions can, under some additional assumptions, give new examples of definable groups with G 00 = G 000 , building upon and extending the intuitions from the first known example with this property, found in [5], namely the universal cover of SL 2 (R). They also pose some questions and conjectures, one of which will be proved at the end of this section.…”
Section: ( † †)mentioning
confidence: 93%
“…And Proposition 2.1(i) of [4] says that H is solvable and there are definable 1 = H 0 < ... < H n = H where each H i+1 /H i is 1-dimensional, torsion-free (definably connected). Also by Proposition 4.7 of [4] H has a global left invariant definable (f -generic) type, so H fits into one of the extreme cases in the previous section.…”
Section: O-minimalitymentioning
confidence: 99%
“…We have the following decomposition theorem [4], Proposition 4.6: Fact 1.18. Suppose G is definably connected.…”
Section: O-minimalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The universal covering group G of a definably connected group G that is interpretable in an o-minimal expansion M of the field R is a NIP group: G is interpretable in the two sorted structure (( 1 (G), +), M ) (E. Hrushovski et al [13]) hence NIP (A. Conversano and A. Pillay [6]). An ultraproduct of groups that are uniformly interpretable in a NIP structure is NIP (D. Macpherson and K. Tent [19]).…”
Section: ) There Is a Nice Subgroup H ⊂ G With S ⊂ H Such That H Is mentioning
confidence: 99%